VOTING FOR NON-MUSLIM LEADERS IN THE QURâ€™ANIC PERSPECTIVE - Makrum, Makrum (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2019)
This paper examines how the law elects non-Muslim leaders from the Qur?an perspective. The issue raised was based on the Regional Head Election (Pilkada) of the DKI Jakarta on February 6, 2017 where one of the candidates is non-Muslim. Then, the simultaneous local elections on June 27, 2018, and the Legislative Election (Pileg) and the Presidential Election (Pilpres) on April 17, 2019. It has become interesting because the issue of ethnic, racial, and religious sentiments (SARA) in the context of candidate leaders often becomes a serious consideration for voters, in addition to capability and track record of the candidate. This paper uses the thematic interpretation method (maudhû?i) seeks to get a comprehensive genealogy of the verse choosing non-Muslim leaders. The results studies that in the Qur'an there are four terms related to leadership: khal?fah, uli al-amr, imâm, and awliyâ?. The last term gives rise to various interpretations because it is mentioned 33 times with various meanings: salvation, friend, and leader. From these verses it can be understood that partiality for non-Muslims (Jews and Christians) is not permitted in Islam, especially in the affairs of the nashb al-Imâmah. As for the fulfillment of the rights of non-Muslims as citizens, it is still guaranteed and highly upheld in Islam.